Adaptasi Indonesia Bergen Social Media Addiction Scale - Sumaryati, Indri Utami; Sirodj, Dwi Agustin Nuriani; Gadama, Melsan (Jurnal Online Psikogenesis, 2024)
Empirical background on emphasizing behavioral addiction becoming more important nowadays. Therefore the measurement toward behavioral addiction become necessary. Social media were online activities and became popular during 10 years earlier. Empirical data shown that media social user performed excessive use of media social that might be lead to addiction. This research aimed to performed measurement adaptation toward Bergen Social Media Addiction scale (BSMAS). The adaptation process were based on the International Test Commision (ITC). Multistage sampling were performed in resulting 483 samples. Statistical analysis conducted were Confirmatory Factor Analysis (CFA), and the result were CR value (0.91)> 0,70 and the VE value (0.65) > 0,50, means the measurement have fulfilled internal consistency and p-value of RMSEA, CFI, GFI and AGFI were fulfilling the criterias . Keywords: Addiction, CFA, Measurement adaptation, Social media.